2023
DOI: 10.1021/acssuschemeng.2c06030
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Cellulose Microfibril through Gamma-Valerolactone-Assisted Co-Solvent and Enzymatic Hydrolysis

Abstract: Biomass recalcitrance during deconstruction remains a key bottleneck to affordable biomass processing technologies. A clear connection between the cell wall structure and biomass deconstruction is necessary to understand how lignocellulosic material is broken down to valuable monomeric components. Here, we monitor changes in the cellulose microfibril domains of poplar, sorghum, and switchgrass throughout gamma-valerolactone (GVL)–water co-solvent pretreatment and enzymatic hydrolysis using solid-state 13C cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Our work has shown that AtCelR is effective as a single enzyme for hydrolysis of amorphous fraction of cellulose derived from gamma valerolactone-pretreated plant biomass ( 56 , 67 ), although the I β -like crystal form of cellulose produced by this pretreatment is resistant to hydrolysis by both AtCelR and commercial enzyme preparations ( 68 ). AtCelR cannot hydrolyze xylan, which limits its utility with less purified forms of plant biomass.…”
Section: Discussionmentioning
confidence: 95%
“…Our work has shown that AtCelR is effective as a single enzyme for hydrolysis of amorphous fraction of cellulose derived from gamma valerolactone-pretreated plant biomass ( 56 , 67 ), although the I β -like crystal form of cellulose produced by this pretreatment is resistant to hydrolysis by both AtCelR and commercial enzyme preparations ( 68 ). AtCelR cannot hydrolyze xylan, which limits its utility with less purified forms of plant biomass.…”
Section: Discussionmentioning
confidence: 95%
“…Besides, replacing the harmful organic solvents with nontoxic, less flammable, and safe reaction media is a key tool for green and sustainable chemical production. In this regard, γ-valerolactone (GVL) is easily synthesized from readily available and potentially renewable feedstocks and it has been used as an additive for food and as a green reaction medium in organic synthesis. On the basis of the above considerations and with the intent to design highly performant catalysts for organic reactions, herein, we presented our efforts to achieve the first photochemical synthesis of symmetrical biaryls by homocoupling of arenediazonium tetrafluoroborates using CuInS 2 QDs as the heterogeneous photocatalyst at room temperature in GVL (Scheme ).…”
Section: Introductionmentioning
confidence: 99%